2020
DOI: 10.1038/s41586-020-2710-1
|View full text |Cite
|
Sign up to set email alerts
|

TRIM37 controls cancer-specific vulnerability to PLK4 inhibition

Abstract: Centrosomes catalyze microtubule formation for mitotic spindle assembly 1 . Centrosomes duplicate once per cell cycle in a process controlled the kinase PLK4 2 , 3 . Following chemical PLK4 inhibition, cell division in the absence of centrosome duplication generates centrosome-less cells that exhibit delayed, acentrosomal spindle assembly 4 . Whether PLK4 inhibitors can be leveraged for cancer treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
126
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(143 citation statements)
references
References 42 publications
13
126
4
Order By: Relevance
“…Moreover, while most centriolar proteins tested did not localize to Centrobin assemblies ( Figure 4—figure supplement 1A and C–E ), we found that SPICE did, although it was not needed for the formation of Centrobin assemblies ( Figure 4—figure supplement 1F,G ). Furthermore, we uncovered that PLK4 is also detected in Centrobin assemblies, which therefore likely coincide with the large PLK4 condensates that form in TRIM37-knock out RPE-1 cells (TRIM37-ko) ( Meitinger et al, 2020 ; Meitinger et al, 2016 ; Figure 4—figure supplement 1H ; Materials and methods). Just like for SPICE, we found that Centrobin assemblies generated upon TRIM37 depletion formed even when PLK4 was targeted using siRNAs ( Figure 4D,E ), despite the presence of monopolar mitotic figures attesting to the efficiency of depletion.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Moreover, while most centriolar proteins tested did not localize to Centrobin assemblies ( Figure 4—figure supplement 1A and C–E ), we found that SPICE did, although it was not needed for the formation of Centrobin assemblies ( Figure 4—figure supplement 1F,G ). Furthermore, we uncovered that PLK4 is also detected in Centrobin assemblies, which therefore likely coincide with the large PLK4 condensates that form in TRIM37-knock out RPE-1 cells (TRIM37-ko) ( Meitinger et al, 2020 ; Meitinger et al, 2016 ; Figure 4—figure supplement 1H ; Materials and methods). Just like for SPICE, we found that Centrobin assemblies generated upon TRIM37 depletion formed even when PLK4 was targeted using siRNAs ( Figure 4D,E ), despite the presence of monopolar mitotic figures attesting to the efficiency of depletion.…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, TRIM37 overexpression has been linked to increased cell invasion and metastasis in colorectal and hepatocellular carcinoma ( Hu and Gan, 2017 ; Jiang et al, 2015 ). Cancer cells overexpressing TRIM37 are hypersensitive to the absence of centrioles upon treatment with the PLK4 inhibitor Centrinone, because excess TRIM37 interferes with acentriolar spindle assembly, inducing mitotic failure ( Meitinger et al, 2020 ; Yeow et al, 2020 ). Moreover, such cells assemble small condensates harboring the centrosomal proteins CEP192 and CEP152, as well as inactive PLK4 ( Meitinger et al, 2020 ; Meitinger et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the eight genes identified, seven genes (RNF7, NCCRP1, BRCA1, TRIM37, RNF25, CDC27, and UBE2H) have been reported to play roles in ubiquitination ( Asamitsu et al, 2003 ; Kallio et al, 2011 ; Link et al, 2016 ; Cho et al, 2018 ; Lim and Joo, 2020 ; Meitinger et al, 2020 ; Zhang et al, 2020 ). It has not been reported that NPEPPS directly participates in the process of ubiquitination, but NPEPPS is also known to degrade the tau protein, which accumulates and polymerizes in some neurodegenerative diseases ( Kudo et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%